Upper Limb Prostheses by the Level of Amputation: A Systematic Review - (:unkn) unknown (MDPI, 2024)
This review article aims to provide an updated and comprehensive overview of the latest trends in adult upper limb prostheses, specifically targeting various amputation levels such as transradial, transmetacarpal, transcarpal, and transhumeral. A systema...
Keywords: Prótesis de miembro superior; Revisión sistemática